1999
DOI: 10.1182/blood.v94.5.1683
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Functions in a Caspase-Independent Manner to Promote Apoptosis-Like Events During Platelet Activation

Abstract: Apoptosis and platelet activation share common morphological and biochemical features. Because caspases are essential mediators of apoptosis, we examined whether platelets contain these proteinases and use them during platelet activation. Human platelets contained caspase-9, caspase-3, and the caspase activators APAF-1 and cytochrome c as shown by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blotting. Upon treatment with cytochrome c and dATP, platelet cytoplasmic extracts recapitulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
115
6
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(136 citation statements)
references
References 46 publications
14
115
6
1
Order By: Relevance
“…This observation provides evidence that platelets, like NCs, do have a mechanism for apoptosis. During the preparation of this report, others 17,18 have reported the expression of caspases 3 and 9 in platelets.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This observation provides evidence that platelets, like NCs, do have a mechanism for apoptosis. During the preparation of this report, others 17,18 have reported the expression of caspases 3 and 9 in platelets.…”
Section: Discussionmentioning
confidence: 89%
“…Annexin V binding measures the surface expression of PS that increases with platelet activation and/or apoptosis. Third, Wolf et al 17 reported that, although the calcium‐dependent proteinase calpain was able to directly proteolyze procaspase 3 and procaspase 9 into smaller subunits during platelet activation, neither of their products was enzymatically active. These results therefore indicate that the increase in caspase enzymatic activity during platelet storage is related to the apoptotic mechanism and not platelet activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the morphological and biochemical changes that characterize the PSL are reminiscent of cell death by apoptosis [3]. Platelets do contain all proteins required for apoptosis, including cytochrome C, procaspase 9, procaspase 8, procaspase 3 and the formation of active caspase 3 [4–6], illustrating that at least the intrinsic pathway of apoptosis seems to be functional [7].…”
Section: Introductionmentioning
confidence: 99%
“…Platelets (PLTs) are enucleated cells, and during ex vivo storage, they undergo morphologic and physiologic changes also known collectively as storage lesions, which adversely affect PLT survival in vivo after transfusion 12‐15 . Apoptosis is a programmed process of cell death of nucleated cells rich in mitochondria and some artificially enucleated cells also manifest this phenomenon 16,17 . Several investigations have focused on studying PLTs in storage to understand the mechanisms underlying storage lesions and to find ways to improve PLT shelf life 12‐18 .…”
mentioning
confidence: 99%